Pengaruh Sudut Pulley dan Mangkok Kartel Terhadap Daya dan SFC Motor 160 cc - Muhammad Yusuf Firdaus; Listiyono Listiyono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Significant developments in the the automotive field from year to year has always increased, accompanied by with the advancement of various supporting components. Apart from functioning as a means of transportation, motorbikes are also a hobby for some people. The objectives of this research are Analyzing the effect of the motorcycle CVT pulley tilt angle on the power and SFC produced by a 160cc motorcycle. produced by a 160cc motorcycle. Analyzing the effect of cartels on the surface of the double bowl of the CVT pulley, on the power and SFC of a 160cc motorcycle. and SFC of a 160cc motorcycle and to obtain the degree of tilt angle on the pulley and the variation of the surface size of the pulley bowl cartel that provides the best performance for 160cc motorcycles. This research uses type of quantitative research with experimental methods. All data collection was carried out on a dynamometer test machine, where the first step was to placing the motorcycle accurately on the predetermined roller bearings. Determined. After the engine and all the measuring equipment were properly installed, the next testing process is to test the power and fuel consumption until data collection. The results of this study get the highest power on a 14° pulley with a 2mm cartel bowl reaching a power of 11.92 HP and get the most optimal SFC value with a value of 0.06813 kg / HP.h. Then the two way anova test was conducted getting an alpha value of less than 0.05. So that the variation has significant influence.